2012
DOI: 10.4239/wjd.v3.i5.80
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related alterations in the enteric nervous system and its microenvironment

Abstract: Gastric intestinal symptoms common among diabetic patients are often caused by intestinal motility abnormalities related to enteric neuropathy. It has recently been demonstrated that the nitrergic subpopulation of myenteric neurons are especially susceptible to the development of diabetic neuropathy. Additionally, different susceptibility of nitrergic neurons located in different intestinal segments to diabetic damage and their different levels of responsiveness to insulin treatment have been revealed. These f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 206 publications
(273 reference statements)
3
38
0
2
Order By: Relevance
“…The TNBS-induced increase in nNOS-IR neurons in the inflamed colon is consistent with previous findings (11). Furthermore, changes in the size and distribution of nNOS neurons have been associated with oxidative stress (5). MSC and CM treatment counteracted morphological changes and inflammationinduced increases in the quantity and proportion of nNOS-IR neurons.…”
Section: Discussionsupporting
confidence: 80%
“…The TNBS-induced increase in nNOS-IR neurons in the inflamed colon is consistent with previous findings (11). Furthermore, changes in the size and distribution of nNOS neurons have been associated with oxidative stress (5). MSC and CM treatment counteracted morphological changes and inflammationinduced increases in the quantity and proportion of nNOS-IR neurons.…”
Section: Discussionsupporting
confidence: 80%
“…HFD impairs neurogenic SM relaxation in WT but not in BK␤ 1 Ϫ/Ϫ mice. We measured neurogenic circular muscle relaxations to test if smaller IJPs are associated with changes in neurogenic relaxations (Fig.…”
Section: -C)mentioning
confidence: 99%
“…Furthermore, we propose that these changes contribute to impaired inhibitory neuromuscular transmission and increased SMC excitability. We tested our hypothesis using colonic tissues from wild-type (WT) and BK␤ 1 Ϫ/Ϫ mice fed a control diet (CD) or a HFD. We found that mice fed a HFD exhibited myenteric plexus oxidative stress, fewer myenteric nitrergic neurons, reduced inhibitory neuromuscular transmission, increased SMC excitability, and impaired colonic motility.…”
mentioning
confidence: 99%
“…In IBS, altered bowel motility and sensory responses cause pain accompanied by diarrhea or constipation, but health is not otherwise affected. ENS defects also occur in Parkinson's disease (8), diabetes (9), and inflammatory bowel disease (IBD) (10), and recent data suggest that ENS damage might play an early etiologic role in IBD (11,12) and Parkinson's disease (13)(14)(15). Here, we focus on cellular and molecular mechanisms controlling ENS development, highlighting areas that require further investigation and potential clinical implications of new discoveries.…”
Section: Introductionmentioning
confidence: 99%